The Antiaggregating Activity of Clopidogrel Is due to a Metabolic Activation by the Hepatic Cytochrome P450-1A - Savi, P; Combalbert, J; Gaich, C; Rouchon, M-C; Maffrand, J-P; Berger, Y; Herbert, J-M (Thrombosis and Haemostasis, 1994)
Clopidogrel and ticlopidine are two well known selective anti-ADP agents which are inactive in vitro and must be administered in vivo to fully exhibit their antiaggregating and antithrombotic effects. Since previous studies have clearly demonstrated that the activation steps take place in the liver, we examined the effect of specific induction or inhibition of cytochrome P450 subfamilies on the antiaggregating activity of clopidogrel. SKF 525-A, a global cytochrome P450 inhibitor, dramatically decreased the antiaggregating effect of clopidogrel, therefore indicating that cytochrome P450 enzymes are involved in the hepatic activation of clopidogrel. The efficacy of clopidogrel was increased in animals pretreated with 3-methylcholanthrene and (3-naphthoflavone, indicating that the cytochrome P450-1A subfamily pathway was mainly involved in the activating metabolism of clopidogrel. The use of specific antibodies directed against the various cytochrome P450 subfamilies ascertained this observation.